Heuristics Hindering the Development of Understanding of Molecular Structures in University Level Chemistry Education: The Lewis Structure as an Example - Maarit Karonen; Mari Murtonen; Ilona Södervik; Marianna Manninen; Mikko Salomäki (MDPI AG, 2021)
Understanding chemical models can be challenging for many university students studying chemistry. This study analysed students' understanding of molecular structures using the Lewis structure as a model, and examined what hinders their understanding. We conducted pre- and post-tests to analyse students' conceptions and changes in them. The measures contained multiple-choice questions and drawing tasks testing their understanding of concepts, such as polarity, geometry, charge or formal charge and expanded octet. The pre-test revealed a lack of knowledge and several misconceptions in students' prior knowledge. For example, the concept of polarity was well-known, but the combination of polarity and geometry appeared to be difficult. For some students, the representation of molecules was intuitive and lacking a systematic approach. Certain students used mnemonics and draw ball-and-stick models connected to surficial representations. After the chemistry courses, the conceptions and drawings had generally changed, and the level of the students' knowledge increased markedly. Although, fewer ball-and-stick models were drawn in the post-test, some students still used them. The main result was that students who drew ball-and-stick models in the pre-test were less capable of drawing the correct Lewis structures with electrons in the post-test. In addition, heuristics seem to hinder learning and some concepts, such as resonance, remained difficult. This is probably due to the fact that understanding molecular structures requires systemic understanding, where several matters must be understood at the same time. Our study highlights that the understanding of molecular structures requires conceptual change related to several sub-concepts.